Case reportsBullous scabies – a case report - Marciniak, Adriana; Czarnecka-Operacz, Magdalena; Silny, Wojciech; Żaba, Ryszard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Scabies is a contagious infestation associated with an ectoparasite, the mite Sarcoptes scabiei. The most noticeable sign of scabies is pruritus, exacerbated mostly at night. Besides the typical clinical picture, there are some reports of scabies presenting as bullous pemphigoid-like eruption. We present a case of scabies with clinical manifestations similar to bullous pemphigoid.